1994
DOI: 10.1021/la00017a022
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Two Calcium Diethylenetriaminepentakis(methylene phosphonic acid) Precipitates and Their Physical Chemical Properties

Abstract: Phosphonates are widely used in industry to treat water for scale and corrosion and in medicine to treat osteoporosis and they are added to toothpaste to control tartar build-up, to mention a few uses. In most of these applications either adsorption or precipitation is proposed to be the primary mechanism of action. In this paper, a combined dialysis and filtration method has been used to prepare and characterize the solubility of a calcium phosphonate, for the first time. The phosphonate used was diethylenetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
60
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 0 publications
9
60
0
Order By: Relevance
“…Close to the structure phosphates are phosphonates, which are also known to form relatively insoluble metal salts. As an example, solubility product constant in the order of 10 −50 had been reported for calcium methylene phosphonate salts [14]. Preliminary analysis in this research has also confirmed the ability of phosphonate to precipitate out other toxic metals such as Cu 2+ , Pb 2+ and Zn 2+ in aqueous solutions.…”
Section: Heavy Metal Precipitation By Ppeisupporting
confidence: 71%
“…Close to the structure phosphates are phosphonates, which are also known to form relatively insoluble metal salts. As an example, solubility product constant in the order of 10 −50 had been reported for calcium methylene phosphonate salts [14]. Preliminary analysis in this research has also confirmed the ability of phosphonate to precipitate out other toxic metals such as Cu 2+ , Pb 2+ and Zn 2+ in aqueous solutions.…”
Section: Heavy Metal Precipitation By Ppeisupporting
confidence: 71%
“…Therefore, small changes in solution composition, due to precipitation/dissolution reactions, change the overall ionic strength only a few percentage. Such small changes in ionic strength have a negligible effect on solution phase ion activity [2,22,27]. In Fig.…”
Section: Resultsmentioning
confidence: 93%
“…The transformation among calcium phosphonate solid phases is still unclear. Kan et al (1994) suggested that an amorphous solid initially precipitates and slowly matures into a thermodynamically stable crystalline phase after calcium mixes with phosphonate. Much higher phosphonate return concentrations at the first 10 pore volumes of return fluid (Figures 1 to 3) may indicate the initial formation of amorphous calcium phosphonate in the column.…”
Section: Figures 2 Andmentioning
confidence: 99%